2020
DOI: 10.1007/s11695-020-05079-x
|View full text |Cite
|
Sign up to set email alerts
|

One Anastomosis/Mini-Gastric Bypass (OAGB/MGB) as Revisional Surgery Following Primary Restrictive Bariatric Procedures: a Systematic Review and Meta-Analysis

Abstract: One anastomosis gastric bypass (OAGB/MGB) has gained popularity in the past decade. International databases were searched for articles published by September 10, 2020, on OAGB/MGB as a revisional procedure after restrictive procedures. Twenty-six studies examining a total of 1771 patients were included. The mean initial BMI was 45.70 kg/m2, which decreased to 31.52, 31.40, and 30.54 kg/m2 at 1, 3, and 5-year follow-ups, respectively. Remission of type-2 diabetes mellitus (T2DM) following OAGB/MGB at 1-, 3-, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 54 publications
3
39
0
3
Order By: Relevance
“…Effectiveness of OAGB/MGB, both in terms of weight loss and obesity-related comorbidities, has been largely demonstrated [13][14][15]. Due to these good outcomes, it has rapidly become one of the most performed primary and revisional procedures worldwide [16,17]. Despite these good results, recalled in a recent consensus conference [4], three major issues raise doubts regarding the safety of OAGB/MGB: risk of biliary reflux, fear of gastro-oesophageal carcinogenesis due to alkaline reflux and rate of post-operative malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Effectiveness of OAGB/MGB, both in terms of weight loss and obesity-related comorbidities, has been largely demonstrated [13][14][15]. Due to these good outcomes, it has rapidly become one of the most performed primary and revisional procedures worldwide [16,17]. Despite these good results, recalled in a recent consensus conference [4], three major issues raise doubts regarding the safety of OAGB/MGB: risk of biliary reflux, fear of gastro-oesophageal carcinogenesis due to alkaline reflux and rate of post-operative malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter study showed an EWL of 77% in a 5-year follow-up after OAGB 20 . Two recently-published systematic reviews showed that OAGB is a valuable choice as a conversion bariatric surgery following a failed restrictive bariatric procedure 21 , 22 . Our study showed mean BMI, EWL% and %TWL of 34.5 ± 8.5 kg/m 2 , %51.6 ± 11.0 and %26.6 ± 5.9 at 1-year follow-up after conversional OAGB respectively.…”
Section: Discussionmentioning
confidence: 99%
“…OAGB is also a therapeutic option ensuring safety and a good effect after insufficient AGB surgery [ 25 ]. OAGB is recognized as a revision after primary restrictive surgery – the Kermansaravi meta-analysis included a total of 1771 revised patients, indicating high efficacy in both weight loss after secondary surgery and satisfactory remission of T2D with follow-up up to 5 years [ 26 ]. It should be remembered that OAGB may be a factor conducive to GERD remission and the development of GERD de novo symptoms.…”
Section: Discussionmentioning
confidence: 99%